Current Strategies to Combat Cisplatin-Induced Ototoxicity - Yu, Dehong; Gu, Jiayi; Chen, Yuming; Kang, Wen; Wang, Xueling; Wu, Hao (Frontiers in Pharmacology, 2020)
Cisplatin is widely used for the treatment of a number of solid malignant tumors. However, ototoxicity induced by cisplatin is an obstacle to effective treatment of tumors. The basis for this toxicity has not been fully elucidated. It is generally accepted that hearing loss is due to excessive production of reactive oxygen species by cells of the cochlea. In addition, recent data suggest that inflammation may trigger inner ear cell death through endoplasmic reticulum stress, autophagy, and necroptosis, which induce apoptosis. Strategies have been extensively explored by which to prevent, alleviate, and treat cisplatin-induced ototoxicity, which minimize interference with antitumor activity. Of these strategies none have been approved by the Federal Drug Administration, although several preclinical studies have been promising. This review highlights recent strategies that reduce cisplatin-induced ototoxicity. The focus of this review is to identify candidate agents as novel molecular targets, drug administration routes, delivery systems, and dosage schedules. Animal models of cisplatin ototoxicity are described that have been used to evaluate drug efficacy and side effect prevention. Finally, clinical reports of otoprotection in patients treated with cisplatin are highlighted. For the future, high-quality studies are required to provide reliable data regarding the safety and effectiveness of pharmacological interventions that reduce cisplatin-induced ototoxicity.